Productivity, innovation and China’s economic growth - Wu, Y.; Guo, Xiumei; Marinova, Dora (2017)
The role of productivity and innovation in China’s economic growth is fiercely debated among economists.1 With the economy currently progressing through the middle-income stages, China is forced to confront difficult areas of restructuring, and this has intensified that debate. Following the Global Financial Crisis (GFC), Chinese policymakers opted to make innovation and entrepreneurship new drivers of economic growth over coming decades.2 This policy shift has merely intensified the debate about and research on productivity growth and innovation in China. This chapter presents an updated literature review and provides new estimates of productivity growth, innovation and efficiency changes in the Chinese economy. In addition, it explores what can be learnt from China’s recent experience and how economic growth may be sustained through innovation and productivity improvement.